Test and Evaluation Methods for Human-Machine Interfaces of Automated Vehicles II (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
With the introduction of automated driving systems (ADSs) and advanced driver assistance systems, the communication of the driver’s responsibilities and the AD’s capabilities has become an important topic in recent years. For example, partially automated driving (SAE L2) systems need to be able to communicate that the driver is still fully responsible for driving safety, whereas higher levels of vehicle automation need to be able to communicate that the driver has to act as a fallback-ready user in case of system limits and malfunctions (SAE L3). During the same trip, different levels of automation might be available to the driver, making it even more crucial that the driving mode is efficiently displayed. These developments require new, standardized tests and evaluating methods for in-vehicle Human–Machine Interfaces (HMIs). This Special Issue includes theoretical papers as well as empirical studies that propose new and innovative test methods in the evaluation of ADS HMIs.